Experimental Study of the Effect of B2O3 on Vanadium-Titanium Magnetite Concentrates Pellets. (27th August 2020) - Liu, Hao; Zhang, Ke; Saxén, Henrik; Liu, Weiqiang; Qin, Yuelin; Xiang, Xiaoyan
Abstract : This paper aims to improve the metallurgical properties of vanadium-titanium magnetite (VTM) concentrates pellets by applying solid waste containing B2 O3 . Thus, the effects of adding B2 O3 on the drop strength, compressive strength, pores area ratio, high-temperature metallurgical properties, and microstructure of VTM pellets were studied through pelletizing and roasting experiments. Results show that the addition of B2 O3 reagent is not conducive to the increase of the drop strength of the green pellets. Nevertheless, the compressive strength and fracture toughness of the roasted pellets can be improved by adding more B2 O3 during the pelletizing. The reduction degree of VTM pellets is firstly decreased and then increased with the added B2 O3 amount. It is possible to improve the compaction degree and restrain the reduction-pulverization degree of the pellet by a low amount of additive (B2 O3 ). The reduction-expansion performance of VTM pellets, in turn, can be raised by adding B2 O3 .